Corticosteroid therapy in IgA Nephropathy: A friend or foe? - Dana Kim; Muh Geot Wong (Karger Publishers, 2023)
Background: The administration of corticosteroids in addition to supportive care to delay progressive Immunoglobulin A nephropathy (IgAN), the most common primary glomerulonephritis worldwide, remains controversial. This is partly due to the paucity of well-designed randomized controlled trials and well-known corticosteroid-related side effects. As a result, clinical equipoise in corticosteroid therapy exists depending on geographical regions and the clinician's preference. Summary: Better understanding around the pathogenesis of IgAN has prompted several clinical trials exploring the effects of immunosuppressive agents including corticosteroids. Earlier studies of corticosteroids were limited by suboptimal study designs, inadequate implementation of standard of care and inconsistent adverse events data collection. Two well designed, adequately powered, multi-centre randomized controlled trials, the STOP-IgAN and TESTING studies, have reported contrasting kidney outcomes that have further fuelled the clinical conundrum regarding the efficacy of corticosteroids. Both studies independently reported greater adverse events with corticosteroids. A novel targeted release formulation of budesonide, which has been hypothesised to reduce the adverse events associated with systemic corticosteroids, has shown promising results in the Phase 3 NefigaRD trial. Studies of treatments targeting B-cells and the complement cascade are currently underway and early data appear encouraging. This review provides an overview of the current literature around the understanding of the pathomechanisms, and benefits and harm of corticosteroid use in IgAN. Key Messages: Recent evidence suggests the use of corticosteroids in a selected cohort of people with IgAN at high risk of disease progression can improve kidney outcomes but comes with an associated risk of treatment-related adverse events particularly with higher doses. Management decisions should therefore follow an informed patient-clinician discussion.